1998
DOI: 10.1002/(sici)1097-4547(19980801)53:3<361::aid-jnr10>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by mercury compounds depends on maturation and is not associated with microglial activation

Abstract: The earliest sign of neurotoxicity observed after exposure of three-dimensional brain cell cultures to low concentrations of mercury compounds is a microglial reaction. We hypothesized that an induction of apoptosis by mercury compounds could be an activating signal of the microglial reaction. Aggregating brain cell cultures of fetal rat telencephalon were treated for 10 days with either mercury chloride or monomethylmercury chloride at noncytotoxic concentrations during two developmental periods: from day 5 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Studies with EtHgCI and PhHgCI and T cells produced similar dose-dependent results. Recent studies in the brain have demonstrated accelerated spontaneous apoptosis of immature astrocytes by HgC12 added to rat brain cell cultures (152). DNA synthesis was decreased, and associated with calcium influx and tyrosine phosphorylation by 10 pM HgCl2 (153).…”
Section: Ironmentioning
confidence: 99%
“…Studies with EtHgCI and PhHgCI and T cells produced similar dose-dependent results. Recent studies in the brain have demonstrated accelerated spontaneous apoptosis of immature astrocytes by HgC12 added to rat brain cell cultures (152). DNA synthesis was decreased, and associated with calcium influx and tyrosine phosphorylation by 10 pM HgCl2 (153).…”
Section: Ironmentioning
confidence: 99%
“…In vitro studies produced the following results: Mercury interferes with polymerization of microtubules [122,123], increases secretion of both 1-40 and 1-42 forms of Aβ and promotes hyperphosphorylation of tau protein [9,[124][125][126][127], changes mitochondrial structure inducing a stress-response in astrocytes [128], and interferes with cell-maturation [129] or other aspects of cell functioning, such as DNA repair, glutathione level, or linkage and structure of microtubules [119,130,131]. Mercury disturbs the interaction between tubulin and GTP [132], and the chelator DMSA can reverse this process [133], while amalgam exposure is toxic for nerve cells in vitro [134].…”
Section: Experimental Animal and In Vitro Studiesmentioning
confidence: 99%
“…40 Exposure of cultured cerebellar granule cells to 28 mM ethanol (a physiological concentration) inhibited differentiation, migration on a laminin substratum, and resulted in death by apoptosis. 37 Methylmercury has been shown in vitro to induce apoptosis in fetal rat telencephalon, 41 developing murine cerebellar granule neurons, 42 and rat cerebellar slice cultures. 43 In cerebellar slices, mercury produced a dose-dependent inhibition of migration of external granule cells and was accompanied by apoptosis of the non-migrating cells.…”
Section: Other Regionsmentioning
confidence: 99%